Instagram Therapists vs. Qualified Mental Health Professionals: How Young Adults Perceive and Navigate Mental Health Advice Online - Lavina Anil Waghalekar; Deeya Bhanushali; Sherin George (International Journal of Behavioral Sciences, 2025)
The growing presence of “Instagram Therapists” - individuals who share mental health advice on Instagram without formal qualifications - has raised important questions about the credibility of online mental health information. In contrast, are qualified mental health professionals and licensed practitioners. Existing literature shows a surge in young adults turning to social media for mental health guidance. However, limited research delves into how they perceive and differentiate between advice from Instagram Therapists and qualified professionals. This qualitative exploratory study aims to investigate how young adults perceive and navigate mental health advice provided by Instagram Therapists in comparison to Qualified mental health professionals. It explores the factors that contribute to building trust in Instagram Therapists, the motivations behind seeking help from qualified professionals instead, and the influence of Instagram-based mental health content on young adults' mental health beliefs, coping strategies, and help-seeking behaviors. 15 young adults aged 18 to 30 years, with no formal background in psychology, participated in semi-structured interviews. Data were analyzed thematically to identify recurring patterns and themes. The findings suggest that while Instagram increases access to mental health information, the lack of Context and depth often leads to emotional consequences. Young adults eventually seek solutions beyond online content, transitioning to therapy for more clarity. Perceptions and misconceptions about therapy also emerged. This study highlights the importance of mental health literacy and verification of professional qualifications before relying on online advice. The results have implications suggesting policies and the need for accurate and responsible Mental Health information on online platforms.
Keywords: Content moderation; help-seeking behaviour; instagram therapists; mental health literacy; mental health professionals; misinformation